Impact of chronic and recurrent dermatophytosis on quality of life and psychologic morbidity—a cross‐sectional study. (13th December 2021) - Das, Anupam; Sil, Abheek; Fatima, Farhat; Podder, Indrashis; Jafferany, Mohammad
Abstract: Background: Chronic and recurrent dermatophytosis is adversely effecting the psychosocial well‐being of patients. Aims: To assess the impact of chronic and recurrent dermatophytosis on quality of life and psychological well‐being of patients. Methods: We performed a cross‐sectional study on patients of chronic and recurrent dermatophytosis aged >12 years. Clinical diagnosis was done, followed by appropriate investigations when required. The patients were made to fill up the questionnaires on Dermatology Life Quality Index, Hospital Anxiety and Depression Scale, and Perceived Stress Scale in English and local languages. The responses were coded with 4‐point Likert scale. Statistical analysis was done using MedCal ® V.125.0. Results: Data of 123 patients were analyzed. Mean DLQI score was 21.4 ± 5.6 and main domain affected was "symptoms and feelings." CRD had an "extremely large effect" on QoL (DLQI score 21–30) in 55.3% patients. Mean HADS‐A(anxiety) score was 10.1 ± 3.6, and mean HADS‐D(depression) score of participants was 7.8 ± 3.2. Mean perceived stress scale (PSS) score was 18.8 ± 4.3. Involvement of >1 site was a risk factor for higher DLQI score suggestive of "extremely large impact" on QoL (OR 34.02, 95% CI 5.7–203.2, p  = 0.0001), higher/worsened HADS‐A score (OR 5.4, 95% CI 1.2–22.9, p  = 0.02), and higher/worsened PSS score (OR 6.1, 95% CI 1.1–34.1, p  = 0.04). Persistent disease >1 year (OR 11.5, 95% CI 1.9–67.8, p  = 0.007) and male gender (OR 0.3, 95% CI 0.1–0.8, p  = 0.01) were significant risk factors for anxiety while BSA involvement >10% was a significant risk factor for moderate to severe perceived stress(OR 13.9, 95% CI 1.5–130.7, p  = 0.02). Conclusion: Chronic and recurrent dermatophytosis requires a multidisciplinary approach involving psychiatrists, to reduce the psychological burden.